2015
DOI: 10.1017/s1355617715000491
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and Pallidal Activation during Reward Modulated Movement Using a Translational Paradigm

Abstract: Objective Human neuroimaging studies of reward processing typically involve tasks that engage decision-making processes in the dorsal striatum or focus upon the ventral striatum's response to feedback expectancy. These studies are often compared to the animal literature; however, some animal studies include both feedback and nonfeedback events that activate the dorsal striatum during feedback expectancy. Differences in task parameters, movement complexity, and motoric effort to attain rewards may partly explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Animal studies and human neuroimaging studies (including subjects with cocaine addiction) suggest that while ventral striatum neurons respond to reward processing, dorsal striatum activate during the timing and other cognitive processes like spatial learning ( van der Meer et al, 2010 ; Coull et al, 2011 ; Tau et al, 2014 ). On the other hand, it is also reported that the reward processing and reward based temporal learning activates both ventral and/or dorsal striatum ( Delgado et al, 2000 ; Bischoff-Grethe et al, 2015 ; Tomasi et al, 2015 ). It was proposed that differences in response requirements might explain the differential activation of ventral/dorsal striatum ( Bischoff-Grethe et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies and human neuroimaging studies (including subjects with cocaine addiction) suggest that while ventral striatum neurons respond to reward processing, dorsal striatum activate during the timing and other cognitive processes like spatial learning ( van der Meer et al, 2010 ; Coull et al, 2011 ; Tau et al, 2014 ). On the other hand, it is also reported that the reward processing and reward based temporal learning activates both ventral and/or dorsal striatum ( Delgado et al, 2000 ; Bischoff-Grethe et al, 2015 ; Tomasi et al, 2015 ). It was proposed that differences in response requirements might explain the differential activation of ventral/dorsal striatum ( Bischoff-Grethe et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is also reported that the reward processing and reward based temporal learning activates both ventral and/or dorsal striatum ( Delgado et al, 2000 ; Bischoff-Grethe et al, 2015 ; Tomasi et al, 2015 ). It was proposed that differences in response requirements might explain the differential activation of ventral/dorsal striatum ( Bischoff-Grethe et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants used a fiber optic joystick (Current Designs, Philadelphia, PA) to control a gray square cursor. A joystick, rather than a button press, was chosen because it engages greater movement control in terms of musculature, which may contribute to the dorsal striatal response during movements elicited by reward anticipation often reported in animal reward processing studies (Bischoff-Grethe et al, 2015; Hollerman et al, 1998; Kawagoe et al, 1998). Three square targets were presented on a black background.…”
Section: Methodsmentioning
confidence: 99%
“…Local field potential recordings from the GPi in humans showed correlation between pallidal LFP amplitude and reward expectation [Schroll et al, ]. Finally, functional neuroimaging has shown greater neural activation in the human pallidum in response to rewards as compared to response to neutral stimuli [Bischoff‐Grethe et al, ].…”
Section: Introductionmentioning
confidence: 99%